Faith-based organizations and social development: The role of Markazosshabab al-Muslim Fil Filibbin in women - Abdel Salam, El Fatih Abdullahi; Mohammad Qassem, Nadhera (David Publishing Company, 2016)
Recently, the issue of women empowerment has gained scholarly interest. This is not only confined to theoretical debate but it has morphed into practical exercise whereby women nowadays have become more empowered and have been assuming an active role in society. However, little is known about the role of faith on women empowerment in this intellectual pursuit. This study takes a leap to investigate if there is a role of faith in empowering women. It tries to examine if faith itself can be a determining factor to embolden women involvement in the society. Being embedded in Islamic principles and values, a faith-based organization in the Philippines called Markazosshabab al-Muslim fil Filibbin is taken as a case study particularly its women department. It examines the role of women in multidimensional aspects. It attempts to explore if women involved in this faith-based organization have become empowered due to the religious principles and values this group is built upon. The study found that women’s lives have been transformed in society. They have become more active in playing their multifaceted role to their family, society, and politics.